New Heterocyclic Compounds: Synthesis, Antioxidant Activity and Computational Insights of Nano-Antioxidant as Ascorbate Peroxidase Inhibitor by Various Cyclodextrins as Drug Delivery Systems - Kaddouri, Yassine; Abrigach, Farid; Yousfi, El Bekaye; Hammouti, Belkheir; El Kodadi, Mohamed; Alsalme, Ali; Al-Zaqri, Nabil; Warad, Ismail; Touzani, Rachid (Current Drug Delivery, 2021)
Aim: The synthesis of seven new antioxidant agents based on the combination of thiazole, pyridine, triazole and pyrazole moieties. The studies of their antioxidant activity using DPPH reduction method. The DFT analysis of the 7 ligands. The docking study was also investigated. The better binding affinity with α-cyclodextrin as best drug delivery system. Background: The screening of new antioxidant compounds and find the good mechanism for binding sites, with correlating between experience and computer theory. Objectives: The DFT analysis of the 7 synthesized ligands.The docking study was also investigated by using the amino acids Ala167 and Arg172. The better binding affinity with α-cyclodextrin as best drug delivery system. Methods: The studies of their antioxidant activity using DPPH reduction method. Results: Chemistry: synthesis of 7 ligands by condensation reaction with 89% yield. Antioxidant activities using DPPH reduction with a good value IC50=13.05 ± 3.73 μg/ml. Using DFT (EHOMO and ELUMO) and Docking APX with the amino acids Ala167 and Arg172 compared to the ascorbic acid. Correlation between all these properties. α-cyclodextrin as best drug delivery system (better binding affinity than caffeic acid). Conclusion: For the drug delivery study, The ACD is best system for all the compounds due to the smallest cavity size which makes the binding affinities favorable and possible to prepare prospective nano-antioxidants.
Keywords: docking